Development and empirical evaluation of a new empathy questionnaire for early adolescents - Mikac, Una (Array, 2013)
The study presents the procedures of construction and initial validation data on a new instrument intended to measure empathy in early adolescent children. The questionnaire was developed by the second and third author of this paper and thus far administered on several independent samples of early adolescents in Croatia. Different authors propose different conceptualizations of empathy: empathy as a personality trait, as a situation-specific state or as a multiphased process (Duan & Hill, 1996). Different structures of empathy were also suggested, and while most of the contemporary authors agree that empathy consists of cognitive and affective dimensions, some authors propose even a more complex structure (e.g., Davis, 1980). In designing this instrument, empathy was conceptualized as rather stable disposition composed of two dimensions, i.e., it was defined as an individual’s ability to both understand and share the feelings of another. The questionnaire was composed of 22 items, 11 intended to measure understanding the feelings of other, and the rest of items intended to measure sharing those feelings. The analyses to be presented are based on empirical data gathered on two independent samples of 5th to 8th grade elementary school students from Zagreb (n1 = 202) and Slavonski Brod (n2 = 133). Average age in both samples was 12 years, with boys and girls equally represented. This presentation will include the results of exploratory and confirmatory factor analyses, along with validity evidence based on relationships with other variables, including grades and some personality traits. Although the results point to similar two-dimensional latent structure in the two samples, the meaning of derived factors does not correspond to the expected dimensions. The results are interpreted in light of existing theories and previous empirical findings published on other empathy measures.